مظاهر البوليسي في رواية "الاختفاء الغامض" للدكتور نبيل فاروق :دراسة نقدية (Al-Qamar, 2024)
This research paper aims to study “Aspects of Detective” in famous Egyptian writer Dr. Nabil Farouk’s novel: “The Mysterious Disappearance”. The detective novel is of the third rank in the Arab world because its writers were preoccupied with the issues and concerns of the sixties and seventies and their relationship to historical morality, and the fact that this art of the novel requires access to legal information from the doors open to detective cases. The detective is a popular subgenre of the novel. The investigation of any crime is called detective. Detective literature is directly related to social reforms. The elements of imagination are evident in “The Mysterious Disappearance” in the hero character who has superior abilities. The author relied on imagination framed by issues of investigation, crimes, and solving mysteries based on major and minor plots and plots that are the engines of imagination. This paper consists of a preface, two chapters and a conclusion. In the 1st chapter gives brief introduction of Dr. Nabil Farouk. The 2nd chapter explains the aspects of the detective story in the novel “The Mysterious Disappearance”.
Keywords: Nabil Farouk; detective Aspects; Mysterious Disappearance